ANALISIS PENGARUH TINGKAT SUKU BUNGA SBI, KURS RUPIAH, HARGA EMAS DUNIA, HARGA MINYAK DUNIA DAN INDEKS HANG SENG TERHADAP INDEKS HARGA SAHAM GABUNGAN (studi kasus pada IHSG di Bursa Efek Indonesia periode 2005-2012) - Rozi, A (JUMANJI (JURNAL MANAJEMEN JAMBI), 2018)
Capital market is macroeconomic indicator, which is very important for a country. This study is intended to test the effect of SBI interest rate, rate of exchange of Rupiah against US Dollar, world gold price, oil price and Hangseng index on Indonesian Composite Index. Samples taken in this research are SBI interest rate, rate of exchange of rupiah against US Dollar, world gold price, oil price, hangseng index and Indonesian Composite Index period of 2005-2012. Data analysis method use is multiple linear regression analysis, classical assumption test, correlation analysis of Pearson, determination coefficient, and hypothetical test accounted uses an application of SPSS 17.0 for windows. The result shows that variable the world gold price and hangseng index partially has found that there is significant influence toward IHSG, while in a whole SBI interest rate, rate of exchange of Rupiah against US Dollar, world gold price, oil price and hangseng index have significant effect to IHSG.